Collection, Viability and Storage Behaviour of Pollen of some Willow Species/Clones - Choudhary, Punit; Singh, N. B. (Indian Forester, 2013)
The genetic improvement of willows through traditional breeding can be facilitated by pollen collection and storage. The female flower receptivity need not be synchronized with pollen shed for breeding. Studies on collection, viability and storage of pollen of commercially important Salix spp. was carried out for implementation of successful breeding programme. The pollen size varied from 20.12 Î¼m to 40.49 Î¼m with clone 131/25 exhibiting maximum size whereas S. babylonica registered minimum size. Germination percentage of the pollen extracted with toluene (Solvent method) was comparatively lower then that of untreated pollen., pollen germination percentage varied between 54.28 to 46.45 per cent in 2009 and 62.88 to 46.88 per cent in 2010. Maximum pollen viability has been recorded at the time of pollen collection. Pollen grains retained higher viability at -20Â°C even after nine months as compared to pollen stored at 4Â°C in both the years. Pollen stored at two different temperatures revealed that there was a linear decrease in pollen viability with increase in storage period. The main pollinators found affecting cross pollination among willows were honey bees (Apies spp.), flies, wasps (Polister spp.) and bumble bee (Bambus spp.)